THE PORTRAYAL OF THE ROLE-PLAY IMPLEMENTATION IN TEACHING SPEAKING TO THE STUDENTS OF TOURISM STUDY PROGRAM - Hainur Diana Insani (Journal of English and Education, 2014)
This paper entitled "The Portrayal of the Role-Play Implementation in Teaching Speaking to the Students of Tourism Study Program" was intended to investigate how role-play is implemented in teaching speaking to the students of Tourism Study Program and the students’ responses towards the implementation of role-play. The participants of this study were an English teacher and eleventh grade students of one vocational high school in Bandung. Qualitative approach was used as the research method by employing non-participant observation and questionnaires to attain the data. The findings showed that the implementation of role-play motivated the students in learning English and help the students bridge the theory into practice. However, the role-play could not be optimally utilized to develop the students’ speaking ability because the teacher violated some principals in teaching speaking and some elements in the implementation of role-play. This research is expected to contribute to the teaching of English especially in the use of role-play in teaching speaking. In addition, it is suggested for the next researcher to extend the research on the use of role-play not only in teaching speaking, but also in the other aspects of communicative language teaching.